The combination of estramustine, vinorelbine, and mitoxantrone in hormone-refractory prostate cancer: A Phase II feasibility study conducted by the Hellenic Cooperative Oncology Group - Samelis, G.F.; Kalofonos, H.; Adamou, A.; Kosmides, P.; Skarlos, D.; Aravantinos, G.; Kiamouris, C.; Adimchi, O.; Fountzilas, G.; Dimopoulos, A.M. (Urology, 2005)
Objectives. To evaluate the safety profile and therapeutic value of the combination of estramustine, mitoxantrone, and vinorelbine in the treatment of hormone-refractory prostate cancer. Methods. Fifty-two patients with hormone-refractory prostate cancer were included in the study. Median age was 70 years (range, 49 to 100 years), World Health Organization performance status ranged from 0 to 2. The treatment schedule consisted of estramustine capsules (140 mg 3 times daily on days 1 to 3 and days 8 to 10 per os), intravenous mitoxantrone (12 mg/m2 on day 2), and intravenous vinorelbine (25 mg/m2 on day 2 and day 9), given in a 3-week cycle. Results. Thirty-one percent of patients with measurable soft-tissue disease demonstrated an objective response, which included six complete and ten partial responses in all involved organs (bone responses not included). Twenty-nine patients (56%) had a greater than 50% reduction in serum prostate-specific antigen level. The median duration of response was 6.9 months, and the median survival for all patients was 14.5 months. Conclusions. The combination of estramustine, vinorelbine, and mitoxantrone is safe, well tolerated, and relatively active in patients with hormone-refractory prostate cancer. © 2005 Elsevier Inc.